Effects of attapulgite dietary supplementation on sow performance in two commercial farms in Greece - KANOULAS, V.; PAPADOPOULOS, G. A.; ARSENOS, G.; TZIKA, E. D.; FORTOMARIS, P. (Journal of the Hellenic Veterinary Medical Society, 2018)
The present study investigated the effects of attapulgite supplementation in sow diets during gestation and lactation on sow performance. The study comprised two reproductive phases (cycles) in two commercial farrow to finish farms: Farm A (capacity: 550 sows) and Farm B (capacity: 220 sows). The treatment groups were: a) control group (CN): the sows were fed a common gestation or lactation diet; b) attapulgite group (AT): the sows were fed the CN diet supplemented with attapulgite at 0,7% level; c) attapulgite plus group (AT+): the sows were fed the CN diet supplemented with attapulgite (0.7%) and a mix of enzymes, live yeast and amino acids (0.1%), at a total of 0.8% level. Within each cycle the sows included per treatment were: 24 for Farm A; 12 for Farm B. Initially data were analyzed per cycle and per each farm. Data from sows that completed both cycles within each farm, were analyzed by repeated measures analysis. Regarding sow parameters, sow body weight loss during lactation tended to be greater in AT sows compared to CN sows during cycle 1 in Farm B and was greater in AT and AT+ than CN sows in Farm A that completed both cycles (P=0.063 and P=0.023, respectively). A greater litter size 24h postpartum was observed in favour of AT compared to CN group during cycle 1 in Farm A and in sows that completed both cycles in Farm A (P=0.001 and P= 0.011, respectively). Litter size at weaning was greater in sows from the AT group than CN during cycle 1 and 2 in Farm A, in cycle 1 in Farm B and in sows that completed both cycles in Farm A (P=0.004, P=0.037, P=0.037, and P=0.022, respectively). Piglet weight at weaning and average daily gain during lactation were greater in AT group than CN and AT+ in sows that completed both cycles in Farm A (P=0.049 and P=0.040 respectively). Notable similar effects, although not statistically significant, were also observed in Farm B. This field study suggests that attapulgite supplementation in sow diets can improve performance indexes. Further research should investigate the underlying mechanisms involved.